PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN PANGAN LOKAL OLAHAN DAN POLA KONSUMSI PANGAN RUMAH TANGGA DI KOTA METRO - Ade Novia Rahmawati; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Lampung University, 2018)
This research aimed to analyze the decision-making process in the processed local food choice, the pattern of food consumption, and the pattern of processed local food consumption; in addition to factors that affected the pattern of household food consumption. This research was conducted by survey method. Location of this research was determined purposively around agroindustry of tapioca vermicelli in Metro City. The amount of research samples in this research was as many as 71 households, and the respondents in this research were housewives who were selected by simple random sampling. The data was collected in month of February – April 2017. And was analyzed by descriptive quantitative analysis, descriptive statistics analysis, and verification analysis by multiple linear regression. The result showed that household decision making in processed local food was consist of introduction needs, seeking information, evaluation of the alternative, selection decision, and post-selection evaluation. The amount of energy consumption was 6,482 kcal/household/day or 1,620 kcal/capita/day. The score of desireable dietary pattern was only 57.45. Cassava was one of the most consumed local foods and has the most processed product. Cassava chips were the processed product of cassava that were consumed in the largest frequency. Most of household got the processed local food by buying. The household desireable dietary pattern around agroindustry of tapioca vermicelli in Metro City was influenced by the household number, the age of housewife, and the high rank of nutrition knowledge of the housewife.Key words: consumtion pattern, decision making, local food